Effects of Animation on Naming and Identification Across Two Graphic Symbol Sets Representing Verbs and Prepositions. - Schlosser, Ralf W.; Koul, Rajinder; Shane, Howard; Sorce, James; Brock, Kristofer; Harmon, Ashley; Moerlein, Dorothy; Hearn, Emilia (Journal of Speech, Language & Hearing Research, 2014)
Purpose: The effects of animation on naming and identification of graphic symbols for verbs and prepositions were studied in 2 graphic symbol sets in preschoolers. Method: Using a 2 × 2 × 2 × 3 completely randomized block design, preschoolers across three age groups were randomly assigned to combinations of symbol set (Autism Language Program [ALP] Animated Graphics or Picture Communication Symbols [PCS]), symbol format (animated or static), and word class (verbs or prepositions). Children were asked to name symbols and to identify a target symbol from an array given the spoken label. Results: Animated symbols were more readily named than static symbols, although this was more pronounced for verbs than for prepositions. ALP symbols were named more accurately than PCS in particular with prepositions. Animation did not facilitate identification. ALP symbols for prepositions were identified better than PCS, but there was no difference for verbs. Finally, older children guessed and identified symbols more effectively than younger children. Conclusions: Animation improves the naming of graphic symbols for verbs. For prepositions, ALP symbols are named more accurately and are more readily identifiable than PCS. Naming and identifying symbols are learned skills that develop over time. Limitations and future research directions are discussed.